Sportorthopädie - Hoffmann C; Lames M (Deutsche Zeitschrift für Sportmedizin)
Evaluation and improvement of aerobic capacity is an essential aspect of performance diagnostics. At the German Swimming Association, the Pansold incremental step-test has been well established and standardized since the 1980s. The unchanged test protocol and the consistent use on all squad members has the advantage of comparability of huge datasets over 3 decades. The aim of this study was to compare the Pansold-test results of the current German national swimming team with the results of former national teams. We analyzed the progression of the main parameters of the lactate-performance-curve for all and single disciplines, and looked for differences between sprinters and distance swimmers, as well as gender differences. The results showthat the current German national swimming team is faster than former national teams, but this seems to be achieved with higher energy expenditure. The maximum mean swimming speed rose significantly over the period studied, and the maximum lactate level increased on average by 2mmol/l. Conversely, the value for aerobic capacity decreased significantly in almost all disciplines. Men and sprinters reach higher peak lactate levels, but seem to have lower aerobic capacity with a flatter lactate performance curve than women and distance swimmers. Overall, the findings demonstrate considerable progressions in German high-performance swimming over the last 3 decades which might depend on higher training volumes in former times.KEY WORDS: Swimming, Pansold-Step-Test, Lactate, Diagnostics, Aerobic Capacity